Peningkatan Hasil Belajar dan Motivasi Belajar Siswa Melalui Pendekatan Behavior Modification di SDIT VIP Al-Huda Candiwulan - Maryanto, Maryanto; Fidianingsih, Yeni; Fatimah, Siti (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2022)
The purpose of this study was to improve student learning outcomes and learning motivation through a behavior modification approach in class IV of SDIT VIP Al-Huda Candiwulan Kebumen, Central Java. This research was carried out using the classroom action research method. This research was conducted in two cycles. Data collection techniques used in this study were tests and observations. The data were analyzed by descriptive statistics, namely calculating the mean and standard deviation. Furthermore, using the standard formula formula, the data is compiled with a frequency distribution table. Data analysis is by comparing the scores obtained from Cycle I and Cycle II (data on learning outcomes and student motivation). The data analysis was the analysis of variance of the paired-samples t-test formula with the help of SPSS PASW Statistics 18. The results of the study were: (1) the level of student learning outcomes through the behaviormodification approach was included in the fairly good category; (2) the level of students' learning motivation through the behavior modification approach is included in the fairly high category; and (3) there is an increase in student learning outcomes and motivation through a behavior modification approach in Class IV SDIT VIP Al-Huda Candiwulan